Improvement in Quality of Life after Myomectomy - Liew, Constance Sat Lin; Alvin Oliver Payus; Rhanye Mac Guad; Ehab Helmy Abdel Malek Fahmy; May Zaw Soe; Satishratnam Nagaratnam; Symeon Mandrinos; Chin Yeung Sing; ABM Tofazzal Hossain (2020)
Dysmenorrhea is one of the leading causes of pelvic pain and menstrual disorder among women during childbearing age. The burden of dysmenorrhea is greater than any other gynaecological complaint. Some women have severe dysmenorrhea which renders them incapacitated for days each menstrual cycle requiring absence from study or duty, frequently requiring pain killer, restriction of daily performance, poor sleep, negative moods such as anxiety and depression. A 31-year-old female presented with severe dysmenorrhea and heavy menstrual bleeding (HMB) as a cause of multiple uterine fibroids, underwent surgeries to remove 100 fibroids from her uterus which has improved her quality of life, eliminating her dysmenorrhea and menstrual abnormalities.